PHENOMENON OF EDUCATIONAL CULTURE AND CADRE TRAINING OF ISLAMIC STUDENTS ASSOCIATION FIS UNIMED BRANCH HMI DELI SERDANG - Maswita; Fadli, Muhammad; Nurhidayah (Edelweiss : Journal Of Innovation In Educational Research, 2025)
This study aims to explore and analyze the phenomenon of cadre culture within the Islamic Student Association (HMI) at the Faculty of Social Sciences, State University of Medan. As the oldest Islamic student organization in Indonesia, HMI's cadre system is not only formal but also deeply rooted in ideological, symbolic, and spiritual values. The research employs a descriptive qualitative approach through case studies involving observation, in-depth interviews, and document analysis. Findings show that cadre formation in HMI FIS UNIMED is perceived as a process of ideological, intellectual, and spiritual self-development, transmitted through symbols, traditions, core ideological values, and continuous mentoring. Nevertheless, this process faces challenges such as decreasing student interest, weak leadership regeneration, and demands for digital adaptation. Despite these challenges, young cadres continue to innovate to ensure that cadre culture remains contextual and relevant.